Criteria for Return to Sport after Anterior Cruciate Ligament reconstruction with lower reinjury risk (CR'STAL study): protocol for a prospective observational study in France. Issue 6 (30th June 2017) - Rambaud, Alexandre J M; Semay, Bertrand; Samozino, Pierre; Morin, Jean-Benoît; Testa, Rodolphe; Philippot, Rémi; Rossi, Jérémy; Edouard, Pascal
Abstract : Introduction: The decision regarding when to return to sport after an anterior cruciate ligament reconstruction (ACLR) is an important one. Using a variety of subjective and objective parameters, various attempts have been made to determine an optimal timeline for a return to sport after ACLR, but none have been validated. The aim of the present study is therefore to determine which criteria or combination of criteria could allow to return to sport with the lowest possible risk of reinjury. Methods and analysis: This study is a prospective cohort, single-centre study, with repeated assessments at 6, 9 and 12 months post-ACL surgical reconstruction and including a 3-year follow-up of patients' sporting activity and reinjuries. 275 patients will be included to test explanatory variables. Postural control analysis, knee laxity, questionnaires (International Knee Documentation Committee (IKDC), Tampa Scale of Kinesiophobia-11 (TSK-11), Anterior Cruciate Ligament—Return to Sport After Reinjury (ACL-RSI) and Single Assessment Numeric Evaluation (SANE)), modified Star Excursion Balance Test, running and sprinting biomechanics, Hop Tests and Isokinetic Tests will all be used. The primary outcome will be any reinjury during the follow-up period, defined as a graft rupture, a contralateral ACL rupture or any injury necessitating an interruption of training and requiring a medical consultation. Two groups will be constituted during the follow-up, separating reinjured from non-reinjured patients. In addition, classic analysis and data mining approaches will be used to build predictive models. Ethics and dissemination: The results of this study will be disseminated through peer-reviewed publications and scientific presentations. Ethical approval was obtained through the ethics committee of the University Hospital of Saint-Etienne (reference number IRBN522015/CHUSTE).